Evaluation of apical sealing ability of ActiV GP/glass ionomer sealer as a root filling material - Souzan Ahmad Kassar; Adnan Asaad Habib; Mazen Deeb Doumani; Saleem Abdulrab; Hisham Alafif (Wolters Kluwer Medknow Publications, 2018)
Introduction: The aim of this in vitro study was to assess the sealing ability of ActiV GP/glass ionomer sealer and to compare it with sealing ability of Resilon/Real Seal and gutta-percha/AH Plus. Materials and Methods: Forty-five human mandibular premolars were randomly divided into three groups (15 canals each). Each canal was instrumented to a size 40, taper 6% using K3 NiTi rotary instruments. A smear layer was removed, and the teeth were filled using single cone technique with ActiV GP, Resilon/Real Seal, or lateral condensation with gutta-percha/AH Plus. The teeth then were immersed in 2% methylene blue solution for 24 h, longitudinally sectioned and examined under a stereomicroscope to evaluate the liner leakage of the dye in each group. The data were analyzed with descriptive statistical methods and Mann-Whitney test (P = 0.05). Results: The lowest mean of leakage was recorded in gutta-percha/AH Plus group. There was a statistically significant difference between gutta-percha/AH Plus group and the two other groups; ActiV GP group and Resilon group. Conclusion: Dye penetration examination showed that ActiV GP/GI sealer had weak sealing properties, Resilon/RealSeal system did not show superior sealing properties in comparison with gutta-percha/AH Plus sealer, and lateral condensation shows better sealing properties in comparison with single cone technique.